Evaluation of the 2013 Curriculum in Islamic Religious Education at SMPN 1 Labuapi: A CIPP Model Analysis (Context, Input, Process, Product) - Khalil, Y Satria Hafizil Khalil; Zainudin; Mukhlis (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2024)
This article aims to examine the implementation evaluation of the 2013 Curriculum in Islamic Religious Education (PAI) at SMPN 1 Labuapi using the CIPP evaluation model (Context, Input, Process, Product). Adopting a qualitative descriptive approach, the study systematically and factually outlines the PAI learning process. The Context evaluation reveals that the curriculum is relevant to current developments and student needs, focusing on improving educational quality and reinforcing character development. The Input evaluation indicates that the readiness of students, facilities, infrastructure, and teaching materials support the success of the learning process, although there are challenges related to student motivation that require further attention. The Process evaluation shows that the learning process is well-implemented, with educators effectively utilising technology, although conventional methods remain dominant. The Product evaluation demonstrates that learning outcomes are being achieved effectively, with students displaying a deep understanding of Islam and a strong character in line with religious and social norms. This research recommends enhancing the quality of PAI learning at SMPN 1 Labuapi by focusing on the development of teaching methods, the utilisation of technology, and the improvement of student motivation to achieve more optimal educational outcomes. Abstrak: artikel ini bertujuan untuk membahas evaluasi implementasi Kurikulum 2013 pada mata pelajaran Pendidikan Agama Islam (PAI) di SMPN 1 Labuapi menggunakan model evaluasi CIPP (Context, Input, Process, Product). Dengan pendekatan kualitatif deskriptif, penelitian ini menggambarkan secara sistematis dan faktual proses pembelajaran PAI. Hasil evaluasi Context menunjukkan bahwa kurikulum ini relevan dengan perkembangan zaman dan kebutuhan siswa, serta berfokus pada peningkatan kualitas pendidikan dan penguatan karakter. Evaluasi Input mengindikasikan kesiapan siswa, sarana, prasarana, dan materi pembelajaran yang mendukung keberhasilan pembelajaran, meskipun ada tantangan terkait dengan motivasi siswa yang perlu perhatian lebih lanjut. Evaluasi Process menunjukkan bahwa pembelajaran dilaksanakan dengan baik, dengan pendidik yang terampil memanfaatkan teknologi, meskipun masih dominan penggunaan metode konvensional. Evaluasi Product menunjukkan hasil pembelajaran yang tercapai dengan baik, dengan siswa menunjukkan pemahaman yang mendalam tentang Islam dan karakter yang kuat sesuai dengan norma agama dan sosial. Penelitian ini merekomendasikan peningkatan kualitas pembelajaran PAI di SMPN 1 Labuapi dengan fokus pada pengembangan metode pengajaran, pemanfaatan teknologi, dan peningkatan motivasi siswa, untuk mencapai hasil pendidikan yang lebih optimal.